Combustion characteristics and gasification kinetics of Brazilian municipal solid waste subjected to different atmospheres by thermogravimetric analysis - Thangarasu, Vinoth [UNESP]; de Oliveira, Miriam Ricciulli [UNESP]; Alves Oliveira, Luís Augusto [UNESP]; Aladawi, Saif; Avila, Ivonete [UNESP] (Elsevier, 2024)
This study examines the gasification kinetics of Brazilian municipal solid waste (MSW) and its components under air, CO2 and air/CO2 (70/30 vol%) atmospheres. The ignition indices of paper and plastic are 6 and 3 times that of food waste, which are 38.6 × 10−3 %/min3 and 19.6 × 10−3 %/min3, respectively, implying a faster separation of volatile compounds from the paper and plastic. The minimum Eα values of 132 kJ/mol and 140 kJ/mol have been obtained for paper waste under air and air/CO2, respectively. On CO2 condition, MSW has an average Ea value of 96 kJ/mol. Under an air/CO2 atmosphere, a high synergistic ΔW of −4.7 wt% has been identified between individual components. The presence of air and CO2 improves the oxidation and char gasification process, thus resulting in better combustion. Hence, the gasification of MSW under an air/CO2 atmosphere would improve the waste-to-energy plant's performance and minimize the CO2 emission.
Keywords: CO2 utilization; Multi-heating rate models; Synergistic effect; Thermal behavior; Thermodynamic analysis